If they are OK, we are OK: the experience of partners living with neuromyelitis optica. Issue 13 (19th June 2017) - Mutch, Kerry; Methley, Abigail; Hamid, Shahd; Moore, Perry; Jacob, Anu
Abstract: Aim: Neuromyelitis optica (NMO) is a rare neuro-inflammatory condition characterized by acute relapses causing severe visual or physical disability. The impact on family members and their experiences have not been studied. The study aims were to explore the lived experience of partners of people with NMO and to investigate potential carer burden in this population. Method: A mixed-method design was used; 11 partners of people with NMO completed semi-structured interviews; 54 partners completed Zarit Burden Interview and Hospital Anxiety and Depression Scale. Results: Three qualitative themes influenced partners' quality of life (QoL): role/relationship; it's all about them; and the impact of NMO. Life changed dramatically for participants after the first NMO attack, necessitating responsibility for physical, financial, social, and emotional support. As NMO symptoms improved and stabilized, freedom and QoL for spouses also improved, albeit with on-going worries regarding the impact of potential devastating future relapses. Quantitative findings showed mild/moderate carer burden (46%), mild/moderate anxiety (59%), and mild/moderate depression (24%). No partner indicated severe carer burden, anxiety, or depression. Conclusion: Participants regarded themselves as partners rather than carers whom require assessment and support for their emotional and health well-being. Health-care professionals need to acknowledge the important role partners play in the dynamics of the family unit, through greater discussion and inclusion. Implications for Rehabilitation: NMO has a strong impact on couples, resulting in both physical caregiving needs and anxiety regarding the unpredictability of potential devastating relapses. Partners do not necessarily experience clinically significant "burden", anxiety or depression, and tools which screen for this may not capture the nature of their experiences. Health-care professionals need to acknowledge, consult, and respect the experience of partners during assessment and implementation of action plans. Partners should be individually assessed based upon the physical and emotional dependency created by NMO to improve their health and well-being.